Ответы и объяснения

  • Участник Знаний
2013-10-21T06:02:34+00:00
 126(x-2)+126(x+2)=16 (x+2)(x-2)
 126(x-2 +x+2)=16 (x+2)(x-2) 
126*2x = 16(x^2-4)
63x = 4x^2 -16
4x^2 - 63x - 16 = 0
D = (-63)^2 - 4*4* -16 = 4225
√D = +/- 65
x1= -1/4
x2= 16
ОТВЕТ  x = {-1/4 ; 16 }

Лучший Ответ!
  • Olimpiya
  • почетный грамотей
2013-10-21T06:08:35+00:00
Приведем к общему знаменателю (х+2)(х-2) и перенесем все в левую часть. При этом х не равно 2 и  -2. 

126/(x+2)+126/(x-2)=16
126(х-2)+126(х+2)-16(х^2-4)=0
126х-252+126х+252-16х^2+64=0
-16х^2+252х+64=0
4х^2-63х-16=0
х1=(63+65)/8=16
х2=(63-65)/8=-0,25